2020
DOI: 10.2196/14355
|View full text |Cite
|
Sign up to set email alerts
|

Hidden Communities of Practice in Social Media Groups: Mixed Methods Study

Abstract: Background Although most US mothers initiate breastfeeding, suboptimal breastfeeding rates still exist. Although breastfeeding is a complex process, social support has been linked with increases in positive breastfeeding outcomes. Recent technological advances, including the development of social networking sites, provide mothers with convenient access to a unique array of audiences from which to seek advice about parenting, including breastfeeding. However, little is known about how the use of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(112 citation statements)
references
References 27 publications
8
65
0
Order By: Relevance
“…A total of 14 publications met the criteria and were chosen for the review. Nine were qualitative (Alianmoghaddam et al, 2019;Black et al, 2020;Bridges, 2016;Clapton-Caputo et al, 2020;Jackson & Hallam, 2020;Niela-Vilén et al, 2015;Regan & Brown, 2019;Skelton et al, 2018), and two were mixed methods (Herron et al, 2015;Skelton et al, 2020). The remaining three were quantitative studies, of which two were randomized controlled trials (RCTs) (Cavalcanti et al, 2019;Niela-Vilén et al, 2016) and one was a cross-sectional survey .…”
Section: Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 14 publications met the criteria and were chosen for the review. Nine were qualitative (Alianmoghaddam et al, 2019;Black et al, 2020;Bridges, 2016;Clapton-Caputo et al, 2020;Jackson & Hallam, 2020;Niela-Vilén et al, 2015;Regan & Brown, 2019;Skelton et al, 2018), and two were mixed methods (Herron et al, 2015;Skelton et al, 2020). The remaining three were quantitative studies, of which two were randomized controlled trials (RCTs) (Cavalcanti et al, 2019;Niela-Vilén et al, 2016) and one was a cross-sectional survey .…”
Section: Included Studiesmentioning
confidence: 99%
“…The remaining three were quantitative studies, of which two were randomized controlled trials (RCTs) (Cavalcanti et al, 2019;Niela-Vilén et al, 2016) and one was a cross-sectional survey . The participants in seven studies were breastfeeding mothers with no specification (Alianmoghaddam et al, 2019;Bridges, 2016;Cavalcanti et al, 2019;Herron et al, 2015;Regan & Brown, 2019;Skelton et al, 2018Skelton et al, , 2020). In the other seven studies, the participants were from specific groups of breastfeeding mothers, including primiparous mothers, mothers with preterm infants, primiparous African American mothers, mothers who exclusively expressed breast milk and ones who continued breastfeeding over 12 months of the child's age (Black et al, 2020;Clapton-Caputo et al, 2020;Jackson & Hallam, 2020;Niela-Vilén et al, 2015;Niela-Vilén et al, 2016;.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of literature has revealed that parents, especially younger mothers, are actively engaged in an online social network (Nolan, Hendricks, Ferguson, & Towell, 2017). Previous work on social media on infant and young child feeding has focused on exploring the parental experiences of using digital media and describing contents made especially within online breastfeeding support group (Asiodu et al, 2015; Regan & Brown, 2019; Skelton, Evans, & LaChenaye, 2020). A recent study has been carried out aimed at evaluating the effects of social media platform on parental feeding behaviours and child dietary intakes (Dumas et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One question was posted in the group every other day. Exclusive groups were created to allow a secure, confidential and safe environment for research participants [ 30 , 31 ]. Each participant was offered a $15 gift card for their time.…”
Section: Methodsmentioning
confidence: 99%